Reputation based Symmetric Key Authentication for Secure Data Transmission in Mobile Ad Hoc Networks - Sangeetha, S.; Sathappan, S. (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: MANETs were a group of nodes which connected each other to establish the network via wireless association to forward packets towards destinations. OBJECTIVES: Reputation-based Symmetric Key Authentication (RSKA) technique is proposed to improve the security of data communication, which securely transmits data packets within MANET communication. Initially, a reputation counts-based node authentication algorithm is designed in RSKA technique by considering the reputation value of mobile nodes in networks. METHODS: By using a reputation count-based node authentication algorithm, the RSKA technique performs the node authentication process before initiating route identification and selects cooperative nodes in MANETs for data transmission. Therefore, the RSKA of nodes results in improved security of data communication for enhancing throughput and reducing data loss rate. Besides, the RSKA technique uses symmetric key cryptography for secure data transmission in which a secret key is generated for the data to be transmitted by the corresponding mobile node along the route path of the source-destination pair. The destination node having the secret key can only decrypt the cypher text. RESULTS: Thus, the RSKA technique improves the data confidentiality rate as well as minimizes the time to protect the data transmission in an efficient way. RSKA was calculated by various parameters, namely data loss rate, throughput and time to protect data delivery as well as data confidentiality rate. CONCLUSION: The simulation result of RSKA improves the data confidentiality rate for achieving secured data transmission as well as minimizes time to protect data delivery within MANETs compared with conventional methods.